Safety and passivation of faecal contamination in waste. Issue 7 (10th July 2020) - Takaya, C.; Carpenter, J.; Muir, R.; Brittle, S.; Sarker, D.K.; Cooper, I.
Abstract : Absorbent hygiene wastes like nappies and incontinence pads are ubiquitous in municipal and healthcare waste streams around the world as they are convenient products used in child-care and adult incontinence management. Absorbent Hygiene Product (AHP) manufacturing is resource-intensive as the products are required to be of the highest value as they are in almost-constant contact with sensitive body parts. The potential for recovering such valuable resources such as cellulose-based fibres and super-absorbent polymers for reuse in non-food sectors like the construction and wastewater industries has been considered in this study. Appropriate decontamination via chemical methods have been examined using AHPs contaminated with human-associated bacteria. Findings suggest that for simulated AHP wastes inoculated with 108–109 CFU g-1 of human-associated bacteria like Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus pyogenes, a 1:1 ratio of 0.5% calcium hypochlorite/AHP waste is adequate to inactivate the bacteria particularly when combined with an inorganic salt for at least 60 min. Specifically, 4 to 5 log10 reductions were observed. Following such disinfection, material storage and temperatures above 25ºC minimise incidences of microbial regrowth. The disinfection protocol was not found to adversely affect the AHP quality. Overall, such findings suggest that AHP recycling is a potential alternative to current AHP waste disposal practices like incineration (with or without energy recovery) and landfilling.